Narrative data and analysis in Second Language teaching and learning - Nugrahenny T. Zacharias (Indonesian JELT, 2016)
The present paper offers a modest contribution to the existing and ongoing attempt to find a place for narrative research in language education. The purpose is mainly to explore and highlight insights gleaned from narrative research with regard to narrative data and analysis. Due to the diverse and unique nature of second language learning and teaching, I would argue that gathering narrative data from second language learners are paramount and in line with the existing attempt to view second language teaching and learning in its own right and not as imitation of first language learning. To develop my argument, I will first discuss the position of narrative research in second language education highlighting the contribution and insights that narrative research brings to second language teaching and learning. I will proceed to define narrative research and explains the various tools to elicit narrative data as well as issues that narrative researcher needs to consider when collecting narrative data. The paper ends by looking at issues and strategies in analyzing narrative data. In all of the discussion, relevant research is cited to illustrate the point being discussed. The paper will end by highlighting that the discussion about narrative data and analysis are not aimed to replace other tools of data elicitation and analysis. Rather, it aims to invite teachers and researchers to see narratives as a viable option in research as the methodology continues to move forward.